Intersectional identities and dilemmas in interactions with healthcare professionals: an interpretative phenomenological analysis of British Muslim gay men. Issue 9 (2nd September 2018) - Semlyen, Joanna; Ali, Atif; Flowers, Paul
Abstract: Individual interviews were conducted with six self-identified Muslim gay men living in London focusing on their experience of health service use. Transcripts were analysed using interpretative phenomenological analysis. Analysis identified two major themes: the close(d) community and self-management with healthcare professionals, detailing participants' concerns regarding the risks of disclosing sexuality; and the authentic identity – 'you're either a Muslim or you're gay, you can't be both' – which delineated notions of incommensurate identity. Analysis highlights the need for health practitioners to have insight into the complexity of intersectional identities, identity disclosure dynamics and the negative consequences of assumptions made, be these heteronormative or faith-related.